Ethanolic Extract Gel Of Planchonia Valida Leaves As An Antibacterial Agent Against Yersiniosis Infection - Sari, Purwita; Hujjatusnaini, Noor; Nirmalasari, Ridha (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Planchonia valida (puting plant) contains ethanol, which is beneficial for treating skin infections and digestive problems, and is capable of inhibiting the growth of gram-negative bacteria such as Yersinia enterocolitica. This study aims to evaluate the adaptability of P. valida extract to Y. enterocolitica in vitro. This experimental research was statistically analyzed using Statistical Product and Service Solutions (SPSS). The adaptability of Y. enterocolitica was observed on nutrient agar (NA) medium in petri dishes treated with P. valida extract at concentrations of 30%, 40%, 50%, 60%, 70%, and 80%, with aquadest as the negative control and chloramphenicol as the positive control. Observations were conducted over three incubation periods (24, 48, and 72 hours) to monitor bacterial growth rate and adaptation. ANOVA results showed p-values at all incubation periods were below the significance level (α = 0.05), indicating significant differences in bacterial adaptation across treatments. The inhibition zone test revealed that the 40% extract concentration was as effective as higher concentrations (50%, 60%, 70%, and 80%). Although the 80% concentration exhibited the largest inhibition zone, its bactericidal effect was not statistically different from the lower concentrations. These results demonstrate the potential of Planchonia valida leaf extract as an effective antimicrobial agent and support further research into its development for the treatment or prevention of Y. enterocolitica infections.